High-molecular-weight organic matter in the particles of comet 67P/Churyumov-Gerasimenko - Fray, Nicolas; Bardyn, Anaïs; Cottin, Hervé; Altwegg, Kathrin; Baklouti, Donia; Briois, Christelle; Colangeli, Luigi; Engrand, Cécile; Fischer, Henning; Glasmachers, Albrecht; Grün, Eberhard; Haerendel, Gerhard; et al. (Nature, 2016)
The COSIMA mass spectrometer on the Rosetta spacecraft has analysed the solid organic matter found in dust particles emitted by comet 67P/Churyumov-Gerasimenko; this matter is similar to the insoluble organic matter extracted from carbonaceous chondrites such as the Murchison meteorite, but is perhaps more primitive.
Published online 7 September 2016; corrected online 5 October 2016
Das PDF enthält zusätzlich einen Anhang von 6 Seiten
Gesehen am 02.09.2020